HD 89345: a bright oscillating star hosting a transiting warm Saturn-sized planet observed by K2. Issue 4 (29th May 2018) - Van Eylen, V; Dai, F; Mathur, S; Gandolfi, D; Albrecht, S; Fridlund, M; García, R A; Guenther, E; Hjorth, M; Justesen, A B; Livingston, J; Lund, M N; et al.
ABSTRACT: We report the discovery and characterization of HD 89345b (K2-234b; EPIC 248777106b), a Saturn-sized planet orbiting a slightly evolved star. HD 89345 is a bright star ( V = 9.3 mag) observed by the K2 mission with 1 min time sampling. It exhibits solar-like oscillations. We conducted asteroseismology to determine the parameters of the star, finding the mass and radius to be 1.12^+0.04_-0.01 M_ and 1.657^+0.020_-0.004 R_, respectively. The star appears to have recently left the main sequence, based on the inferred age, 9.4^+0.4_-1.3 Gyr, and the non-detection of mixed modes. The star hosts a 'warm Saturn' ( P = 11.8 d, R p = 6.86 ± 0.14 R⊕ ). Radial-velocity follow-up observations performed with the FIbre-fed Echelle Spectrograph, HARPS, and HARPS-N spectrographs show that the planet has a mass of 35.7 ± 3.3 M⊕ . The data also show that the planet's orbit is eccentric ( e ≈ 0.2). An investigation of the rotational splitting of the oscillation frequencies of the star yields no conclusive evidence on the stellar inclination angle. We further obtained Rossiter–McLaughlin observations, which result in a broad posterior of the stellar obliquity. The planet seems to confirm to the same patterns that have been observed for other sub-Saturns regarding planet mass and multiplicity, orbital eccentricity, and stellar metallicity.